2013
DOI: 10.1007/s10637-013-9944-9
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of the amido phosphoribosyltransferase inhibition by PY873, PY899 and a derivative of isophthalic acid

Abstract: Selectively decreasing the availability of precursors for the de novo biosynthesis of purine nucleotides is a valid approach towards seeking a cure for leukaemia. Nucleotides and deoxynucleotides are required by living cells for syntheses of RNA, DNA, and cofactors such as NADP(+), FAD(+), coenzyme A and ATP. Nucleotides contain purine and pyrimidine bases, which can be synthesized through salvage pathway as well. Amido phosphoribosyltransferase (APRT), also known as glutamine phosphoribosylpyrophosphate amido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Despite its complexity, the underlying basis of cell growth inhibition by these compounds relies on their ability to block de novo synthesis of the purine nucleotides, i.e., precursors of DNA (Schoettle et al, 1997). This work is an extension of our previous study where we reported inhibition of amido phosphoribosyltransferase using 2,4-Diamino analogs of folic acid (Batool et al, 2013).…”
Section: Introductionmentioning
confidence: 61%
“…Despite its complexity, the underlying basis of cell growth inhibition by these compounds relies on their ability to block de novo synthesis of the purine nucleotides, i.e., precursors of DNA (Schoettle et al, 1997). This work is an extension of our previous study where we reported inhibition of amido phosphoribosyltransferase using 2,4-Diamino analogs of folic acid (Batool et al, 2013).…”
Section: Introductionmentioning
confidence: 61%
“…Major potential therapeutic applications of enzymes are in the treatment of cancer and also in neurological disorders [2][3][4]. Genetic engineering and insilico approaches are used for the synthesis and modifications of the enzymes as therapeutic agents for Alzheimer's disease (AD) [5].…”
mentioning
confidence: 99%